Unheimliche Bedrohungen und heimliche Widerstände — Zur religiösen Situation in Kabardino-Balkarien - Alikajew, Raschid; Mühlfried, Florian (Georgica, 2016)
Based on subjective experience in Kabardino-Balkaria, the authors attempt to identify current threat scenarios there and demonstrate the local mechanisms used to defend against their adverse effects. For this purpose, the paper analyses the tendencies of radicalisation rooted in Islam, alongside the story of Raqbazi−a sacred tree−which simultaneously illuminates the history of Balkaria over the past one hundred years. By way of conclusion, the authors note that, to protect against the adverse effects of existing threats, the following means are employed in Balkaria: concealment, alienation, and exoticization.